New therapeutic approaches for EGFR mutated non-small cell lung cancer on osimertinib era - Jaime Rubio-Perez; Roberto Hernandez; Carlota Santolaya; Maria Cruz Martin-Soberon; Sandra Zazo; Nerea Carvajal; Federico Rojo (Cancer Treatment and Research Communications)
Introduction: EGFR-mutated non-small cell lung cancer (EGFRmut NSCLC) represents a heterogeneous group of tumors with varying clinical outcomes. Resistance to osimertinib, a third-generation EGFR tyrosine kinase inhibitor (EGFR-TKI), is inevitable, with emerging evidence suggesting that concurrent genomic alterations influence treatment efficacy. Materials and Methods: This retrospective study analyzed 58 stage IV EGFRmut NSCLC patients treated with osimertinib across four hospitals in Madrid, Spain, between March 2021 and February 2023. Comprehensive genomic profiling was conducted using next-generation sequencing (NGS) to evaluate co-mutations. Kaplan-Meier survival curves and Cox regression were applied to assess progression-free survival (PFS) and overall survival (OS). Results: A second co-mutation was identified in 44.1 % of patients, with TP53 (70 %) being the most frequent, followed by EGFR (11.5 %), PI3K (11.5 %), and MET amplifications (7.7 %). Patients with co-mutations exhibited significantly worse PFS compared to those with only EGFR mutations (HR: 8.0, 95 % CI: 1.81–35.4; p = 0.001). Specifically, TP53 co-mutations were associated with reduced PFS (HR: 21.6, 95 % CI: 2.77–169; p < 0.001) and a non-statistically significant trend toward worse OS (HR: 3.10, 95 % CI: 0.89–10.8; p = 0.062). Discussion: This study highlights the prognostic impact of co-mutations, particularly TP53, in EGFRmut NSCLC treated with osimertinib. These findings underscore the need for novel therapeutic approaches and personalized treatment strategies, especially in subgroups with poor prognoses. Trials such as MARIPOSA and FLAURA-2 provide promising evidence for treatment intensification, but careful patient stratification is essential to balance efficacy and toxicity.